'The Fearful Silence of Three Women (Mark 16:8)'. (14th September 2020) - O'Collins, Gerald
Abstract: This article aims at reinstating an older interpretation (offered e.g. by R. H. Lightfoot) of the astonishment, fear, and silent flight with which three women responded to the message they heard from the angel in Jesus's open and empty tomb. It was an appropriate reaction to the astonishing revelation of the resurrection. The article argues that this reaction is not to be reckoned as an unexpected failure on the part of the women. Throughout Mark's Gospel they proved exemplary in their following of Jesus, right through to being present at his crucifixion. Mary Magdalene and her two companions remained temporarily silent until they could deliver the angel's message to the appropriate audience, the male disciples.